BODIPY‐Functionalized Natural Polymer Coatings for Multimodal Therapy of Drug‐Resistant Bacterial Infection - Lujiao Zhang; Chenyan Hu; Meizhou Sun; Xiaokang Ding; Hong‐Bo Cheng; Shun Duan; Fu‐Jian Xu (Advanced Science, 2023)
Abstract The fact that multidrug resistance (MDR) could induce medical device‐related infections, along with the invalidation of traditional antibiotics has become an intractable global medical issue. Therefore, there is a pressing need for innovative strategies of antibacterial functionalization of medical devices. For this purpose, a multimodal antibacterial coating that combines photothermal and photodynamic therapies (PTT/PDT) is developed here based on novel heavy atom‐free photosensitizer compound, BDP‐6 (a kind of boron‐dipyrromethene). The photothermal conversion efficiency of BDP‐6 is of 55.9%, which could improve biocompatibility during PTT/PDT process by reducing the exciting light power density. Furthermore, BDP‐6, together with oxidized hyaluronic acid, is crosslinked with a natural polymer, gelatin, to fabricate a uniform coating (denoted as polyurethane (PU)‐GHB) on the surface of polyurethane. PU‐GHB has excellent synergistic in vitro PTT/PDT antibacterial performance against both susceptible bacteria and MDR bacteria. The antibacterial mechanisms are revealed as that hyperthermia could reduce the bacterial activity and enhance the permeability of inner membrane to reactive oxygen species by disturbing cell membrane. Meanwhile, in an infected abdominal wall hernia model, the notable anti‐infection performance, good in vivo compatibility, and photoacoustic imaging property of PU‐GHB are verified. A promising strategy of developing multifunctional antibacterial coatings on implanted medical devices is provided here.